PENERAPAN TES DAN PENGUKURAN DALAM EVALUASI KEMAMPUAN SMASH ATLET BOLA VOLI - Alya Ulil Albab; Davin Muhammad Firdaus; Dita Al Rahmadani; Syarif Fudin; M Irfan; Ely Yuliawan (STKIP Subang, 2026)
This study was motivated by the importance of applying tests and measurements to evaluate volleyball players’ smash skills in order to determine their skill level, the effectiveness of training, and the development of their performance. The smash is one of the key techniques in volleyball that significantly determines a team’s success in scoring points. However, in practice, the use of systematic testing and measurement instruments in the athlete evaluation process is still suboptimal. This study aims to describe the application of tests and measurements in evaluating volleyball athletes’ smash ability and to identify their benefits in improving the quality of training and athlete performance. The research method used is a descriptive qualitative method with a literature review approach (library research). Data were obtained through a review of various sources such as books, scientific journals, articles, and documents relevant to testing, measurement, sports evaluation, and volleyball smash techniques. Data analysis was conducted through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the application of tests and measurements in evaluating the smash ability of volleyball athletes plays a crucial role in determining the accuracy, power, and effectiveness of their smashes. Furthermore, these tests and measurements assist coaches in designing training programs that are more targeted, objective, and tailored to the athletes’ needs, thereby optimizing volleyball performance